PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, UMUR PERUSAHAAN, DAN UKURAN DEWAN KOMISARIS TERHADAP PENGUNGKAPAN AKUNTANSI SUMBER DAYA MANUSIA - Nelly Anggraini; Christina Fransiska (Balance: Media Informasi Akuntansi dan Keuangan, 2021)
The objectives of this study are: (1) Analyzing profitability variables has a significant positive effect on the disclosure of Human Resource Accounting to Manufacturing companies listed on the Indonesia Stock Exchange; (2) Analyzing the Company Size variables has a significant positive effect on the disclosure of Human Resource Accounting to Manufacturing companies listed on the Indonesia Stock Exchange; (3) Analyzing the Company's Age variables has a significant negative effect on the disclosure of Human Resource Accounting to Manufacturing companies listed on the Indonesia Stock Exchange; (4) Analyzing the Variable Size of the Board of Commissioners has a significant positive effect on the disclosure of Human Resource Accounting to Manufacturing companies listed on the Indonesia Stock Exchange. This research uses quantitative. The results of this study are: (1) Variable profitability has a positive effect and does not affect the disclosure of Human Resource Accounting. (2) The company size variable and Variable size of the commissistic board has a positive and significant effect on the disclosure of Human Resource Accounting; (3) The company's age variable has a negative and insignificant effect on the disclosure of Human Resource Accounting